2007
DOI: 10.1021/ol062947x
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Thapsigargin, a Potent SERCA Pump Inhibitor

Abstract: The enantioselective total synthesis of thapsigargin, a potent, selective inhibitor of the Ca2+ pump SERCA, is described. Starting from ketoalcohol 8, key steps involve regioselective introduction of the internal olefin at C4-C5, judicious protecting group choice to allow chelation-controlled reduction at C3, and chemoselective introduction of the angelate ester function at C3-O. A selective esterification approach completes the total synthesis in a total of 42 steps and 0.61% overall yield (88.6% average yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 21 publications
(17 reference statements)
0
26
0
1
Order By: Relevance
“…This compound was originally isolated from the roots of Thapsia garganica L. (Apiaceae) by the group of Prof. Søren Brøgger Christensen (Danish University of Pharmaceutical Sciences, Copenhagen, Denmark) [112], with the structure and relative configuration determined by chemica1 and spectroscopic investigations, together with X-ray analysis of its 7,11-epoxide analogue [113]. The absolute configuration of TPG was established using CD spectroscopy with the application of Horeau’s method [114], and the enantioselective total synthesis of TPG has been completed through a total of 42 steps of reactions involving regioselective introduction of the internal olefin at C-4–C-5, judicious protecting group choice to allow chelation-controlled reduction at C-3, and selective esterification (Scheme 11) [115, 116]. …”
Section: 8-o-(12-{l-leucinoylamino}dodecanoyl)-8-o-debutanoylthapsmentioning
confidence: 99%
“…This compound was originally isolated from the roots of Thapsia garganica L. (Apiaceae) by the group of Prof. Søren Brøgger Christensen (Danish University of Pharmaceutical Sciences, Copenhagen, Denmark) [112], with the structure and relative configuration determined by chemica1 and spectroscopic investigations, together with X-ray analysis of its 7,11-epoxide analogue [113]. The absolute configuration of TPG was established using CD spectroscopy with the application of Horeau’s method [114], and the enantioselective total synthesis of TPG has been completed through a total of 42 steps of reactions involving regioselective introduction of the internal olefin at C-4–C-5, judicious protecting group choice to allow chelation-controlled reduction at C-3, and selective esterification (Scheme 11) [115, 116]. …”
Section: 8-o-(12-{l-leucinoylamino}dodecanoyl)-8-o-debutanoylthapsmentioning
confidence: 99%
“…Because of their small size, these compounds can be prepared from inexpensive starting materials in only a few synthetic steps. This constitutes a considerable advantage over TG-based inhibitors, whose complex total synthesis entails 42 steps, has an overall yield of 0.6%, and requires the use of multiple protecting groups 7.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Thapsigargin (TG), a highly specific SERCA pump inhibitor, irreversibly blocks the calcium pumping from the cytosol into the ER lumen. TG binds to the functional cavity of SERCA on the ER membrane and locks the pump into a conformation with poor calcium and ATP affinity [67,68]. Although SERCA and the plasma membrane calcium ATPase pump (PMCA) share many structural similarities, TG is ineffective against PMCA.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the PMCA pump lacks Glu residue involved in calcium translocation in the SERCA [69]. The structural difference between SERCA and PMCA and specific structural requirement for TG binding may explain the different actions of TG [6771]. …”
Section: Methodsmentioning
confidence: 99%